MANAJEMEN HUBUNGAN SEKOLAH DAN MASYARAKAT DI SEKOLAH MENENGAH PERTAMA NEGERI 7 BANJARMASIN - Nauriatul Muharramah; Isny Lellya; Heri Jamanul Haidi (Management of Education: Jurnal Manajemen Pendidikan Islam, 2023)
Public relations management in educational institutions is one of the core and important components in education management, where the process of public relations management for education is the process of planning, implementing, monitoring, and evaluating programs that are centered on social interaction. This study aims to find out how the school and community relations management program is implemented in schools, which in its implementation includes aspects of management functions, namely planning, organizing, implementing, monitoring and evaluating the implementation of the Public Relations Management program at SMP Negeri 7 Banjarmasin. This study uses a type of field research (field research) with a descriptive qualitative research approach. The subjects of this study were the Principal, Deputy Head of Public Relations and Public Relations Staff in the implementation of the Public Relations Management program at SMP Negeri 7 Banjarmasin. The results of this study can be concluded that the implementation of the Public Relations program at SMP Negeri 7 Banjarmasin begins with planning, at this stage the appointment as Deputy Head of Public Relations is carried out and the formation of a team and a meeting determines the program. Next is organizing, namely the distribution of tasks and authority to each member of Public Relations. Furthermore, the implementation is to realize the program that has been previously set, in this stage the Principal and Deputy Public Relations carry out routine supervision / monitoring with a predetermined schedule. Then evaluation, namely analysis and assessment of the process of implementing the Public Relations program.